Applying the Trait-Factor Theory to Promote Entrepreneurial Career Choices: A Framework for Vocational Guidance in Undergraduate Education - Saka Abdulganiyu; Haruna Saidu; Atabor Micheal (Global Academy of Multidisciplinary Studies, 2026)
Purpose This paper examines the adaptation of Trait-Factor Theory for entrepreneurial career guidance in undergraduate education, focusing on the alignment of students' personal traits with suitable entrepreneurial paths in a rapidly changing economic landscape. Research Methodology: The study utilizes a qualitative approach, analyzing Trait-Factor Theory’s application through literature review and case studies of institutions integrating entrepreneurial guidance into their curricula. Results: Findings indicate that assessing personality, cognitive, motivational, and behavioral factors help personalize career paths for students. The study highlights the importance of a tailored matching system that aligns students’ traits with entrepreneurial opportunities, boosting their potential for success in entrepreneurship. Conclusions: The study concludes that adapting Trait-Factor Theory to entrepreneurship education enhances individualized support for students, equipping them to navigate the complexities of modern entrepreneurship. It suggests incorporating experiential learning and curriculum integration for effective career guidance. Limitations: Limitations include the qualitative nature of the research, based on selected case studies, which may not fully represent global undergraduate programs. Additionally, the traditional Trait-Factor Theory may need further adjustments to meet the evolving needs of entrepreneurial education. Contributions: This paper contributes by proposing a revised application of Trait-Factor Theory in entrepreneurship education, emphasizing a developmental, inclusive, and context-sensitive approach. It advocates for continuous program evaluation and cross-sector collaboration to better prepare students for entrepreneurship.